Activated carbons for effective pharmaceutical adsorption: Impact of feedstock origin, activation agents, adsorption conditions, and cost analysis - Issam Mechnou; Anasse Benabdallah; Az-Iddin Chham; Younes Rachdi; Miloudi Hlaibi; Abdeslam El kartouti; Na’il Saleh (Results in Engineering, 2025)
Activated carbon adsorption is an effective technique for capturing pharmaceutical molecules. The cost-effectiveness of this adsorbent depends largely on the choice of raw material,activating agents, and adsorption conditions, which influence their morphologies and chemical surface properties. However, the relationship between the type of raw materials, activating agents, and adsorption conditions and the properties of activated carbons is not fully defined. In this paper, we review, based on recent studies, the relationship between raw materials and the physicochemical properties (active sites and porosity) of activated carbons designed to eliminate pharmaceuticals. We also examine the percentage distribution of chemical functions in active ingredients and carry out a cost-effectiveness evaluation, using paracetamol as a control to compare the raw materials studied. Activated carbons from various raw materials exhibit surface functions such as C=O, C-N, COOH, NH2, Si-O and O-H, with surface areas over 3400 m2 g−1 and a capacity reaching 2000 mg g−1. The results identified three classes of raw materials. Carbonizable liquid waste was identified as a first-class raw material, enabling the development of activated carbons with significant physico-chemical properties and adsorption capacities, but limited by low yields. Fossil coals, agricultural waste and lignin constitute the second class, with variable costs. Finally, aquatic biomass and petrochemicals (third class) is unfavorable because of its low yield and expensive production. Overall, for clean, profitable and efficient production, the choice of raw materials is important in the development of activated carbons.